Innovative Coating Method of MgAl2O4 or ZnAl2O4 on α-Al2O3 Spheric Nuclei - Baez,Graciela Mabel (2015)
Structured materials composed of α-Al2O3 spheres covered with a porous and thin layer of MgAl2O4 or ZnAl2O4 were obtained. The innovative coating method developed consists in the formation of a precursor gel of MgAl2O4 or ZnAl2O4 by citrate-nitrate combustion method. The alumina spheres are submerged in this gel and then submitted to a drying process in vacuum and to calcinations with N2 and N2/O2. SEM results showed that a very rough and porous layer uniformly covers the spheres. The thickness of the layer reaches the maximum value of 16 µm in the sample coated with two layers of ZnAl2O4. XRD results confirmed the MgAl2O4 or ZnAl2O4 spinel formation in the layered material. The structured materials were used as Pt catalysts supports, showing a good catalytic activity in the n-butane dehydrogenation reaction.